SOFT SKILLS , MENANAMKAN SIKAP BERTANGGUNG JAWAB BAGI CALON PEKERJA MIGRAN INDONESIA - Ramayani Yusuf; Gunardi Gunardi; Yaya Mulya Mantri; Ayulia Nirwani (ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Responsible behavior is an essential life skill that must be possessed by Indonesian Migrant Worker Candidates (CPMI), both in personal and financial contexts. This community service activity aims to enhance the understanding and capability of CPMI under the supervision of PJTKI AL Zubaran in developing responsible character through the Financial Life Skills (FLS) program. The problems faced by CPMI include lack of understanding about responsible behavior, low financial literacy, weak work character, and minimal preparation to face challenges in destination countries. The implementation method uses a participatory and interactive learning approach through simulation games, group discussions, case studies, personal reflection, and practical exercises for 90 minutes. The training materials cover basic concepts of responsibility, five key values forming responsibility (honesty, respect, fairness, accountability, and courage), application of responsible behavior in various contexts, responsible financial decision-making, and practical strategies to become a reliable individual. This activity is expected to equip CPMI with a comprehensive understanding that every action has consequences that must be accounted for, as well as increase their readiness in facing ethical dilemma situations in the workplace and wise financial management. The expected benefits include improving the quality of CPMI as professional workers who have integrity, positive reputation, and the ability to manage finances responsibly for a better future.